Relation between water pollution and the incidence of diseases in the communities of Augusto Franco and Treze de Julho, neighborhoods of Aracaju/Se, Brazil - Santos, A. F.; Anjos, B. M.; Mattos, C. D.; Dantas, I. M. S.; Fontes, K. V. L. C.; Correia, M. G. S. (Scientia Plena, 2012)
This study aims to establish a comparative picture between the diseases caused by ingestion of contaminated water in two districts of Aracaju-SE: the lower middle-class community of Augusto Franco and upper middle class Treze de Julho. The field research was a qualitative-quantitative approach. As data collection instrument it was used structured interviews and data collected were applied to statistical and comparative procedures. The results obtained in the Treze de Julho neighborhood were more favorable in terms of water quality. The conditions were related to the incidence of diseases including identifying the communities. These communities reported that only type of water treatment that they have access is provided by DESO, and as the liquid comes with different characteristics in these districts may be due to leakage and/or infiltration of the plumbing system of Augusto Franco. In Treze de Julho, condominiums can be taking some procedures related to the water tank and the use of artesian wells. The neglect of the authorities before the existence of sources of contamination easily perceived in these addresses can result in public health problems.